Isolated cortical tuber in an infant with genetically confirmed tuberous sclerosis complex 1 presenting with symptomatic West syndrome. Issue 1 (12th November 2020) - Miyata, Hajime; Fushimi, Soichiro; Ota, Yoko; Vinters, Harry V.; Adachi, Kaori; Nanba, Eiji; Akiyama, Tomoyuki
Abstract : Tuberous sclerosis complex (TSC) is an autosomal dominant hereditary disorder caused by mutations in either TSC1 on chromosome 16 or TSC2 on chromosome 9, clinically characterized mainly by facial angiofibroma, epilepsy, and intellectual disability. Cortical dysplasias, subependymal nodules, and subependymal giant cell astrocytoma are characteristic central nervous system lesions among 11 major features in the current clinical diagnostic criteria for TSC. We encountered an unusual case of genetically confirmed TSC1 presenting with symptomatic West syndrome due to an isolated cortical dysplasia in the left occipital lobe of a six‐month‐old male infant who did not meet the clinical diagnostic criteria for TSC. The patient underwent left occipital lesionectomy at age 11 months and has been seizure‐free for nearly six years since then. Histological examination of the resection specimen revealed cortical neuronal dyslamination with abundant dysmorphic neurons and ballooned cells, consistent with focal cortical dysplasia (FCD) type IIb. However, the lesion was also accompanied by unusual features, including marked calcifications, dense fibrillary gliosis containing abundant Rosenthal fibers, CD34‐positive glial cells with abundant long processes confined to the dysplastic cortex, and multiple nodular lesions occupying the underlying white matter, consisting exclusively of ballooned cell and/or balloon‐like astrocytes with focal calcifications. Genetic testing for TSC1 and TSC2 using the patient's peripheral blood revealed a germline heterozygous mutation in exon 7 (NM_000368.5: c.526dupT, p.Tyr176fs) in TSC1 . Isolated FCD with unusual features such as calcification, dense fibrillary gliosis, Rosenthal fibers and/or subependymal nodule‐like lesions in the white matter may indicate the possibility of a cortical tuber even without a clinical diagnosis of TSC. Identification of such histopathological findings has significant implications for early and accurate diagnosis and treatment of TSC, and is likely to serve as an important supplementary feature for the current clinical diagnostic criteria for TSC.